V2G Multi-Objective Dispatching Optimization Strategy Based on User Behavior Model - Li, Tianyu; Tao, Shengyu; He, Kun; Lu, Mengke; Xie, Binglei; Yang, Biao; Sun, Yaojie (Frontiers in Energy Research, 2021)
V2G (Vehicle to Grid) technology can adjust the grid load through the unified control of the charging and discharging of electric vehicles, and achieve peak shaving and valley filling to smooth load fluctuations. Aiming at the random and uncertain problem of EV user travel and behavior decision-making, this paper proposes a V2G multi-objective dispatching strategy based on user behavior. First, a V2G behavior model was established based on user behavior questionnaire surveys, and the effective effect of EV load was simulated through Monte Carlo simulation. Secondly, combined with the regional daily load curve and peak-valley time-of-use electricity prices, with the goal of stabilizing grid load fluctuations and increasing the benefits of EV users, a multi-objective optimal dispatching model for electric vehicle cluster charging and discharging is established. Considering the needs of electric vehicles and the operation constraints of the distribution network, the genetic algorithm is used to obtain the Pareto optimal solution. The results show that when dispatching with the maximum benefit of users, the peak-to-valley ratio of the grid side can be reduced by 2.99%, and the variance can be reduced by 9.52%. The optimization strategy can use peak and valley time-of-use electricity prices to guide the intelligent charging and discharging of electric vehicles while meeting user needs, so as to achieve the optimal multi-objective benefit of V2G participation in power response.